Pemahaman Kosakata Budaya Bagi Calon Peserta Magang ke Jepang di Kota Medan - Muhammad Yusuf; Taulia Taulia; Laraiba Nasution; Alvy Mawaddah; Abdul Gapur; Khairunnisa Nur Hasanah (STMIK Budi Darma, 2023)
In Medan, there are Vocational Training Institutions (Lembaga Pelatihan Kerja abbreviated as LPK) actively sending interns or workers to Japan. Before departing to work in Japan, prospective participants are prepared in various aspects, including their proficiency in the Japanese language. One of the efforts made in this program is to enhance the communication skills of prospective interns in the Japanese language, specifically their understanding of culturally relevant vocabulary in Japan. Although Japanese language instruction is provided at a basic level, the focus of learning is placed on comprehending culturally significant terms. The service team collaborates with partner LPKs in Medan to implement this teaching program. The training program involves the participation of 20 individuals. The results of the training activities indicate high satisfaction, with enthusiastic and actively engaged participants who contribute to discussions. The participants actively participate in each teaching session, demonstrating a strong interest in learning Japanese cultural vocabulary. The outcomes of these activities have shown enthusiasm and active participation, successfully enhancing the participants' understanding of Japanese cultural vocabulary. This training program provides a solid foundation for prospective interns to adapt well to the work and cultural environment in Japan. It is expected that this program will provide tangible benefits to the prospective interns, the involved LPKs, and the wider community. The emphasis on cultural vocabulary comprehension is anticipated to increase employment opportunities abroad and contribute to the overall development of Indonesia's human resources.